"I own it, don't I?" The Rules of Academic Copyright Ownership and You. Issue 4 (2nd October 2018) - Benson, Sara R.
Abstract: This article delves into a few areas of copyright law that academic authors often overlook: joint author's rights and the work made for hire doctrine. Scholarly publications produced by university professors often include more than one author. The default copyright laws apply to any such works if there is no specific written agreement to the contrary. Thus, it is important to understand what those default rules are in order to determine whether it is appropriate to deviate from them in an author agreement. Similarly, the work made for hire doctrine would normally apply to make all work produced by professors owned by the university. Luckily, many universities do not wish to own such work and give it back to professors through university statutes and other governing documents. However, it is crucial to understand whether the default rules apply or the university permits professors to negotiate their own author agreements with publishers. Finally, if authors own their own scholarly works, publishers can expect that they will negotiate their rights in the publishing agreements to benefit the terms most favorable to the author. And yet, many faculty members simply sign a standard authorship agreement without asking for concessions on the part of the publisher. Thus, this article empowers professors to exercise their copyright rights to the full extent of the law and to negotiate their author's agreements to benefit themselves and society as a whole through open access and the use of Creative Commons licenses.